Oviposition, antixenosis and antibiosis traits in coconut palm cultivars against red palm weevil, Rhynchophorus ferrugineus - Lizanne, M; Nai, T k; Mathe, V (Indian Journal of Plant Protection, 2020)
Short Commucation